1999
DOI: 10.1111/1467-9280.00149
|View full text |Cite
|
Sign up to set email alerts
|

N400 Effects Reflect Activation Spread During Retrieval of Arithmetic Facts

Abstract: Arithmetic facts are stored in densely interconnected memory networks, and retrieval errors may occur because activation spreads to associated results. We studied the extension of activation spread by means of the so-called N400 effect of the event-related brain potential (ERP). With semantic stimuli, N400 amplitude has proved to be inversely proportional to the amount of activation that originates from a priming context. ERPs were recorded from 61 scalp positions while 16 subjects verified 600 multiplication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
150
4
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 23 publications
17
150
4
1
Order By: Relevance
“…Recall that Galfano et al (2003) found that presentation of a problem activates not only the answer, but also the neighbors of this problem, which provides direct evidence for this assumption. Niedeggen and Rösler (1999) have provided event-related potential (ERP) evidence for this same assumption, which we will discuss below in more detail. The second assumption is that not all problems are represented; rather, for each commutative pair of problems (e.g., 7 ϫ 5 and 5 ϫ 7), there is only one representational unit.…”
Section: Basic Principlesmentioning
confidence: 90%
“…Recall that Galfano et al (2003) found that presentation of a problem activates not only the answer, but also the neighbors of this problem, which provides direct evidence for this assumption. Niedeggen and Rösler (1999) have provided event-related potential (ERP) evidence for this same assumption, which we will discuss below in more detail. The second assumption is that not all problems are represented; rather, for each commutative pair of problems (e.g., 7 ϫ 5 and 5 ϫ 7), there is only one representational unit.…”
Section: Basic Principlesmentioning
confidence: 90%
“…First, in verbal-production tasks, the tongue movement and muscle activities might add artifacts to the EEG recording. For this reason alone, many other similar studies have used delayed verification tasks (e.g., Galfano, Mazza, Angrilli, & Umiltà, 2004;Niedeggen & Rosler, 1999;Szucs & Csepe, 2005). Second, multiplication problems generally involve larger numbers as their answers (ranging from 6 to 72) than do other operations such as addition (5-17) and subtraction (1-7).…”
Section: Methodsmentioning
confidence: 99%
“…2006;Sanders & Astheimer, 2008). The effects of attentional control incurred, for instance, by stimulus competition, stimulus-response conflict or error detection, are more commonly observed in an ERP modulation effect around 400-550 ms after stimulus onset (Frühholz et al, 2009;Larson et al, 2009;Liotti et al, 2000;Niedeggen & Rösler, 1999;West & Alain, 1999). Our findings suggest that the DARPP-32 gene is associated with the amplitude of these components.…”
Section: Genetic Correlates Of Cortical Evoked Potentialsmentioning
confidence: 61%
“…Furthermore, we were interested in analyzing DARPP-32 genotype effects on the late N450 modulation effect, which has been previously shown to reflect the deployment of attentional resources when cognitive conflict (e.g., Larson et al, 2009;West & Alain, 1999), error monitoring (Niedeggen & Rösler, 1999) or attention orienting (Kanske et al, 2011) was involved. Previous studies showed a more posterior distribution of the N450 component when not using the classical Stroop but other conflict paradigms (e.g., Frühholz et al, 2009;Schirmer & Kotz, 2003).…”
Section: Analyses Of Eeg Datamentioning
confidence: 99%